Major QTLs and Potential Candidate Genes for Heat Stress Tolerance Identified in Chickpea (Cicer arietinum L.) - Jha, Uday Chand; Nayyar, Harsh; Palakurthi, Ramesh; Jha, Rintu; Valluri, Vinod; Bajaj, Prasad; Chitikineni, Annapurna; Singh, Narendra P.; Varshney, Rajeev K.; Thudi, Mahendar (Frontiers in Plant Science, 2021)
In the context of climate change, heat stress during the reproductive stages of chickpea (Cicer arietinum L.) leads to significant yield losses. In order to identify the genomic regions responsible for heat stress tolerance, a recombinant inbred line population derived from DCP 92-3 (heat sensitive) and ICCV 92944 (heat tolerant) was genotyped using the genotyping-by-sequencing approach and evaluated for two consecutive years (2017 and 2018) under normal and late sown or heat stress environments. A high-density genetic map comprising 788 single-nucleotide polymorphism markers spanning 1,125 cM was constructed. Using composite interval mapping, a total of 77 QTLs (37 major and 40 minor) were identified for 12 of 13 traits. A genomic region on CaLG07 harbors quantitative trait loci (QTLs) explaining >30% phenotypic variation for days to pod initiation, 100 seed weight, and for nitrogen balance index explaining >10% PVE. In addition, we also reported for the first time major QTLs for proxy traits (physiological traits such as chlorophyll content, nitrogen balance index, normalized difference vegetative index, and cell membrane stability). Furthermore, 32 candidate genes in the QTL regions that encode the heat shock protein genes, heat shock transcription factors, are involved in flowering time regulation as well as pollen-specific genes. The major QTLs reported in this study, after validation, may be useful in molecular breeding for developing heat-tolerant superior lines or varieties.